PATH-22. COMPREHENSIVE ANALYSIS OF DIVERSE LOW-GRADE NEUROEPITHELIAL TUMORS WITH FGFR1 ALTERATIONS REVEALS A DISTINCT MOLECULAR SIGNATURE OF ROSETTE-FORMING GLIONEURONAL TUMOR. (9th November 2020) - Lucas, Calixto-Hope G; Gupta, Rohit; Doo, Pamela; Wood, Matthew; Grafe, Marjorie; Lee, Han; Kleinschmidt-Demasters, B K; Bush, Nancy Ann Oberheim; Taylor, Jennie; Clarke, Jennifer; Butowski, Nicholas; Kline, Cassie; et al.
Abstract: The FGFR1 gene encoding fibroblast growth factor receptor 1 has emerged as a frequently altered oncogene in the pathogenesis of multiple low-grade neuroepithelial tumor (LGNET) subtypes including pilocytic astrocytoma (PA), dysembryoplastic neuroepithelial tumor (DNT), rosette-forming glioneuronal tumor (RGNT), and extraventricular neurocytoma (EVN). These activating FGFR1 alterations in LGNET can include tandem duplication of the exons encoding the intracellular tyrosine kinase domain, in-frame gene fusions most often with TACC1 as the partner, or hotspot missense mutations within the tyrosine kinase domain (either p.N546 or p.K656). However, the specificity of these different FGFR1 events for the various LGNET subtypes and accompanying genetic alterations are not well defined, nor are the histopathologic features of pilocytic astrocytomas with FGFR1 alterations versus those harboring the more common BRAF mutations or fusions. Here we performed comprehensive genomic and epigenomic characterization on a diverse cohort of 30 LGNET with FGFR1 alterations. We identified that RGNT harbors a distinct epigenetic signature compared to other LGNET with FGFR1 alterations, and is uniquely characterized by FGFR1 kinase domain hotspot missense mutations in combination with either PIK3CA or PIK3R1 mutation, often with accompanying NF1 or PTPN11 mutation. In contrast, EVN harbors its own distinct epigenetic signature and is characterized by FGFR1 - TACC1 fusion as the solitary pathogenic alteration. Additionally, DNT and PA are characterized by either kinase domain tandem duplication or hotspot missense mutations, occasionally with accompanying NF1 or PTPN11 mutation, but lacking the accompanying PIK3CA or PIK3R1 mutation that characterizes RGNT. The glial component of LGNET with FGFR1 alterations typically has a predominantly oligodendroglial morphology, and many of the pilocytic astrocytomas with FGFR1 alterations lack the biphasic pattern, piloid processes, and Rosenthal fibers that characterize pilocytic astrocytomas with BRAF mutation or fusion. Together, this analysis refines the classification and histopathologic spectrum of LGNET with FGFR1 alterations.